Quality and Safety Issues of Direct Oral Anticoagulants in the Emergency Department - Cervellin, Gianfranco; Benatti, Mario; Bonfanti, Laura; Lippi, Giuseppe (Seminars in Thrombosis and Hemostasis, 2015)
The direct oral anticoagulants (DOACs) are increasingly used in patients with atrial fibrillation and venous thromboembolism. The decision making of clinicians and especially emergency physicians for the appropriate management of patients taking DOACs entails a thorough understanding of pharmacologic profile, practical guidance on their usage, and management of bleeding and/or thrombotic events. The available evidence suggests that the bleeding complications observed in patients taking DOACs are less frequent and potentially less severe than those in patients taking vitamin K antagonists or heparins. This should be regarded as an advantage for emergency physicians, since it would decrease the admission rate of anticoagulated patients and probably require a less aggressive treatment in the emergency department (ED). The greatest challenge of DOACs is so far represented by the lack of clinically usable antidotes, since these (i.e., idarucizumab, andexanet alfa, and aripazine) are in different phases of development. A second major concern is the current lack of consensus about laboratory monitoring for these drugs. Although there is widespread perception that patients on DOACs do not require dose adjustment based on laboratory testing, in some selected clinical situations, laboratory testing may be taken into consideration in the ED. The type of laboratory diagnostics needed for emergency management should hence include tests that are promptly available, affordable to all stat laboratories, and cost effective. The aim of this article is to provide a personal overview on quality and safety issues of DOACs with an ED perspective.
Keywords: direct oral anticoagulants; new oral anticoagulants; dabigatran; rivaroxaban; apixaban; edoxaban